Fashion communication in the digital age : FACTUM 19 Fashion Communication Conference, Ascona, Switzerland, July 21-26, 2019 /: FACTUM 19 Fashion Communication Conference, Ascona, Switzerland, July 21-26, 2019. (2019) - Unknown
No abstract available